Human glandular kallikrein 2 levels in serum for discrimination of pathologically organ-confined from locally-advanced prostate cancer in total PSA-levels below 10 ng/ml. - Haese, A; Graefen, M; Steuber, T; Becker, C; Pettersson, K; Piironen, T; Noldus, J; Huland, H; Lilja, H (2001)
BACKGROUND: We measured serum levels of human glandular kallikrein 2 (hK2) in patients treated with radical retropubic prostatectomy (rrP) for clinically localized prostate cancer (PCa) with a total PSA (tPSA)-level below 10 ng/ml to investigate whether hK2 can be applied to preoperatively distinguish organ-confined (pT2a/b) from nonorgan-confined (> or = pT3a)-PCa more accurately than total PSA. Further, we evaluated hK2, free- and tPSA-concentrations in all pathologic stages of PCa. METHODS: 161 serum samples from men scheduled for rrP were collected 1 day before surgery prior to any prostatic manipulation. Pathologic work-up revealed > or = pT3a-PCa in 48 and pT2a/b-PCa in 113 patients. HK2-levels in serum were measured using an immunofluorometric assay with an analytical sensitivity of 0.5 pg/ml, a functional sensitivity of 5 pg/ml and insignificant cross-reactivity with PSA (< 0.005%). Total (tPSA) and free PSA (fPSA) levels were measured using a commercially available assay from which we calculated %fPSA and an algorithm that combined hK2 and PSA-levels [hK2] x [tPSA/fPSA]. Means, medians, and ranges were calculated for pT2a/b vs. >/= pT3a-PCa and for all pathologic stages. Statistical significance of differences was calculated using Mann-Whitney-U and Kruskal-Wallis tests. Calculation of receiver-operator-characteristic (ROC) curves were performed for hK2, [hK2] x [tPSA/fPSA] and tPSA to compare diagnostic performance. RESULTS: A mean tPSA level in serum of 6.12 ng/ml in > or = pT3a-PCa was not significantly different (P = 0.366) from 5.78 ng/ml in pT2a/b-PCa. Also, there were no statistically significantly different levels of fPSA (P = 0.947) or %fPSA (0.292) for these two groups. By contrast, mean hK2-level in pT2a/b-PCa of 80 pg/ml was significantly different (P = 0.004) from a mean hK2 level of 120 pg/ml in > or = pT3a-PCa as shown by Mann-Whitney-analysis Moreover, the algorithm of [hK2] x [tPSA/fPSA] was significantly lower (P = 0.0004) in pT2a/b-PCa vs. > or = pT3a-PCa. Calculation of areas under curve (AUC) by receiver-operator-characteristics (ROC) demonstrated that the AUC for hK2 (0.64) was larger and the AUC for [hK2] x [tPSA/fPSA] (=0.68) significantly larger (P = 0.007) compared to the AUC of tPSA (0.55). Furthermore, Kruskal-Wallis Test revealed a highly significant correlation to pathologic stage using hK2 (P = 0.008) and [hK2] x [tPSA/fPSA] (P = 0.0015) compared to no significant differences in serum concentration of tPSA (P = 0.296). Also at tPSA-levels from 10-20 ng/ml, the hK2-levels in pT2a/b-PCa were close to significantly different (P = 0.051) from those in men with >/= pT3a-PCa, while the algorithm of [hK2] x [tPSA/fPSA] in that tPSA-range was significantly lower (P = 0.002) in pT2a/b-PCa compared to > or = pT3a0-PCa. CONCLUSIONS: Highly significant differences in serum concentration enable hK2 to be a powerful predictor of organ-confined disease and pathologic stage of clinically localized prostate cancer, especially in the PSA-range below 10 ng/ml. As such, there are important clinical consequences for the application of hK2 for the adequate treatment of prostate cancer patients, i.e., the option of nerve-sparing surgery. (c) 2001 Wiley-Liss, Inc.